The effect of musical practice on gesture/sound pairing - Proverbio, Alice M.; Attardo, Lapo; Cozzi, Matteo; Zani, Alberto (Frontiers in Psychology, 2015)
Learning to play a musical instrument is a demanding process requiring years of intense practice. Dramatic changes in brain connectivity, volume, and functionality have been shown in skilled musicians. It is thought that music learning involves the formation of novel audio visuomotor associations, but not much is known about the gradual acquisition of this ability. In the present study, we investigated whether formal music training enhances audiovisual multisensory processing. To this end, pupils at different stages of education were examined based on the hypothesis that the strength of audio/visuomotor associations would be augmented as a function of the number of years of conservatory study (expertise). The study participants were violin and clarinet students of pre-academic and academic levels and of different chronological ages, ages of acquisition, and academic levels. A violinist and a clarinetist each played the same score, and each participant viewed the video corresponding to his or her instrument. Pitch, intensity, rhythm, and sound duration were matched across instruments. In half of the trials, the soundtrack did not match (in pitch) the corresponding musical gestures. Data analysis indicated a correlation between the number of years of formal training (expertise) and the ability to detect an audiomotor incongruence in music performance (relative to the musical instrument practiced), thus suggesting a direct correlation between knowing how to play and perceptual sensitivity.